Direct and indirect effects of estrogens, androgens and intestinal microbiota on colorectal cancer - Wu, Zihong; Sun, Yi; Huang, Wenbo; Jin, Zhenzhen; You, Fengming; Li, Xueke; Xiao, Chong (Frontiers in Cellular and Infection Microbiology, 2024)
Sex differences in colorectal cancer (CRC) has received considerable research attention recently, particularly regarding the influence of sex hormones and the intestinal microbiota. Estrogen, at the genetic and epigenetic levels, directly inhibits CRC cell proliferation by enhancing DNA mismatch repair, regulating miRNAs, blocking the cell cycle, and modulating ion channels. However, estradiol’s activation of GPER promotes oncogene expression. Conversely, androgen contributes to epigenetic dysregulation and CRC progression via nuclear receptors while inducing apoptosis through membrane receptors. Specific gut microorganisms produce genotoxins and oncogenic metabolites that damage colonic cell DNA and contribute to cancer induction. Regarding the tumor microenvironment, estrogen mitigates intestinal inflammation, reverses immunosuppression, increases gut microbiome diversity and commensal bacteria abundance, and decreases pathogen enrichment. On the contrary, androgen disrupts intestinal microecology, diminish immunotherapy efficacy, and exacerbate colonic inflammation and tumor growth. The impact of estrogen and androgen is closely tied to their receptor status, elucidating their dual roles in CRC pathogenesis. This review comprehensively discusses the direct and indirect effects of sex hormones and the intestinal microbiota on CRC, considering environmental factors such as diet and lifestyle to propose novel prevention and treatment strategies.